Evidence for changes in behaviour leading to reductions in HIV prevalence in urban Malawi. Issue 4 (23rd March 2011) - Bello, George; Simwaka, Bertha; Ndhlovu, Tchaka; Salaniponi, Felix; Hallett, Timothy B
Abstract : Background: At the epicentre of the HIV epidemic in Eastern Africa, HIV prevalence has appeared to stabilise in most countries. However, there are indications that the HIV epidemic in Malawi has recently declined. Methods: We analysed sexual behaviour survey data from Malawi between 2000 and 2004 and HIV prevalence data from the national antenatal clinic HIV surveillance system between 1994 and 2007 using a mathematical modelling technique that can identify associations between behaviour change and reductions in incidence. Results: In Malawi between 2000 and 2004 there were significant reductions in the proportion of 15–19 year olds starting sex, the proportion of men having sex with more than one woman in the previous year and significant increases in condom use by men with multiple partners. In the same period, prevalence dropped from 26% to 15% in urban areas among pregnant women and reduced by 40% among women aged 15–24 years. In the same period, prevalence remained at ∼12% in rural areas. Mathematical modelling suggests that the declines in prevalence in urban areas were associated with the behaviour changes and that, if the changes are maintained, this will have cumulatively averted 140 000 (95% interval: 65 000 to 160 000) HIV infections by 2010. Conclusion: Changes in sexual behaviour can avert thousands of new HIV infections in mature generalised hyper-endemic settings. In urban Malawi, the reduction in the number of men with multiple partners is likely to have driven the reduction in incidence. Understanding the causes of this change is a priority so that successful programmes and campaigns can be rapidly expanded to rural areas and other countries in the region.